Case Study On AKN Technology Berhad - Omar Khan, Hussein (2006)
The research is aimed to provide a valuable insight into AKN\'s operations and be able to identify the issues surrounding the company and recommended strategies for its future growth. In addition to that, it is also possible to put the tools and methodologies learned into practice.